First report of the parasite crustacean Leidya distorta (Isopoda: Bopyridae) on the fiddler crab Uca spinicarpa (Decapoda: Brachyura) in Yucatán coasts, Mexico - Jesús Romero-Rodríguez; Sergio Guillén-Hernández; Nuno Simões (Revista Mexicana de Biodiversidad)
Parasitic isopods, particularly members of the Bopyridae that infest crustacean hosts, have received scant study in many geographic regions. As part of a project aimed at documenting parasites of fish and invertebrates from the coast of Yucatán, Mexico, 2,467 individuals of the fiddler crab Uca spinicarpa were collected from March 2002 to July 2007. Based on the sampled specimens, we report the presence of Leidya distorta in the branchial chamber of U. spinicarpa for the first time. We found a prevalence of 3.77%, mean intensity of 1.47, and mean abundance of 0.06 for this parasite. With the addition of L. distorta, the number of bopyrids reported from Mexican coasts increases to 44 species. Males of U. spinicarpa were more often infested than females, which could be due to the sex ratio being strongly skewed towards males in the host sample studied (0.85:0.15 M:F). Morphological differences between males and juveniles, as well as between sub-adult and adult females of L. distorta are described.